EMPLOYEES’ LABOR RIGHTS AND MECHANISMS FOR THEIR PROTECTION - Askarhujaeva Gulira'no Abiddinovna (Bright Mind Publishing, 2025)
This article research analyzes employees’ labor rights and the mechanisms designed to protect them within modern labor relations. The study focuses on the fundamental rights guaranteed by national legislation and international standards, such as fair working conditions, occupational safety, remuneration, and social protection. Special attention is given to legal, institutional, and organizational mechanisms for ensuring labor rights, including dispute resolution procedures, labor inspections, and the role of trade unions. The article identifies existing challenges in the labor protection system and proposes solutions aimed at improving legal awareness, reducing informal employment, and strengthening state control. The results highlight the importance of effective labor rights protection for social stability and economic development.
Keywords: Labor rights, employee protection, labor legislation, dispute resolution, trade unions, occupational safety, social guarantees, labor mechanisms.